Friday

August 22, 2014

August 22, 2014

Posted by **abhi** on Monday, December 24, 2012 at 3:19pm.

- maths -
**MathMate**, Monday, December 24, 2012 at 9:32pmy=x+tan(x)

y'=1+sec(x)^2

y"=0+2sec(x)*(-1/cos²(x))(-sin(x))

=sec²(x)tan(x)

=>

cos²(x)y"-2y+2x

=2cos²(x)sec²(x)tan(x)-2(x+tan(x)+2x

=2tan(x)-2x-2tan(x)+2x

=0

- maths -
**MathMate**, Monday, December 24, 2012 at 9:33pmShould read:

y"=0+2sec(x)*(-1/cos˛(x))(-sin(x))

=**2**sec˛(x)tan(x)

**Related Questions**

maths - trigonometry - I've asked about this same question before, and someone ...

Pre-Calc - Trigonometric Identities Prove: (tanx + secx -1)/(tanx - secx + 1)= ...

Pre-Calc - How do I solve this? My work has led me to a dead end. tan(45-x) + ...

Math - find the second derivative of ln(sinx) i worked this out and i got -tanx

Math - Prove each of the following identities. a)tan^2x = 1 – cos^2x/cos^2x b)...

Math - 1)A piano tuner uses a tuning fork. If middle C has a frequency of 264 ...

Mathematics - Trigonometric Identities - Prove: sinx + tanx = tanx (1 + cosx) ...

matj - prove that (cotx+tanx)(cotx-tanx) = 1/(sin^2 x) - 1/(cos^x)

calculus - Differentiate both sides of the double angle identify sin 2x= 2 sin x...

trig - prove: cot^2(x)=cos(x)/(sinx)(tanx)